Exploring Gender Preferences for Collaborative and Assessment E-Learning Tools: A South African Perspective - Tendayi C. Garutsa (Journal of Education and Learning Technology)
Females and males have different proficiency levels in their use of technology. Females exhibit lower confidence and self-efficacy toward digital technologies compared to males. This study aims to explore gender differences in the preference for e-learning tools for collaborative learning and assessment purposes in the Faculty of Humanities at North-West University, South Africa. A sequential explanatory research design was employed, with questionnaires administered in the first phase and interviews conducted in the second phase. The qualitative data was analysed using content thematic analysis. The quantitative data was analysed using simple descriptive statistics and the Mann-Whitney U test, a non-parametric statistical test, to compare differences between female and male students in e-learning tool preferences. The findings from the analysis of gender-based preferences for collaborative learning and e-learning assessment tools revealed distinct trends, with some tools showing significant gender-based preferences while others do not. These results suggest that while gender may influence the choice of certain educational technologies, the factors underlying these preferences are multifaceted, involving utility, ease of use, and the perceived effectiveness of the tools. This study recommends that institutions of higher learning incorporate gender-sensitive tools like Zoom Chat and Graphical Assessments, while providing training for educators on multimedia design and collaborative platforms. Additionally, enhancing IT infrastructure, offering user guides, and conducting workshops or peer mentoring sessions can improve accessibility, collaboration, and technical support for all students.